COMPARATIVE CHARACTERISTICS OF CLINICAL AND LABORATORY MARKERS OF NUTRITION IN PREMATURE CHILDREN TAKING INTO ACCOUNT GESTATIONAL AGE AT BIRTH - Godovanets, Oleksii; Nechytaylo, Yuriy (Eastern Ukrainian Medical Journal, 2025)
Introduction. Current data from scientific literature indicate the need to create unified recommendations for diagnosing feeding intolerance in premature infants. It is known that clinical manifestations of digestive system dysfunction in the postnatal period are the cause of the subsequent development of persistent functional gastrointestinal disorders, which worsens the patients` quality of life. In general, recommendations for providing medical care to newborns with feeding intolerance in perinatal pathology are an important area of scientific research at the present stage. Objective. To determine the main clinical and laboratory criteria for feeding intolerance in premature infants based on coprofiltrate parameters, considering gestational age and severity of the condition at birth. Materials and Methods. A comparative analysis of clinical and laboratory criteria for feeding intolerance in perinatal pathology was conducted in premature children of different gestational ages. The list of laboratory parameters of coprofiltrate included: the levels of fecal calprotectin, albumin, α-1-antitrypsin, fecal elastase-1, and PMN-elastase. Results. Clinical signs of feeding intolerance in premature infants include gastric residual volume > 50%, regurgitation and/or Banti syndrome, flatulence, blood in stools, acholic stools, and signs of endotoxemia. Laboratory markers of gastrointestinal disorders determined based on coprofiltrate studies are: increased levels of fecal calprotectin, albumin, α-1-antitrypsin, fecal elastase-1, and decreased PMN-elastase. Conclusions. The results of our study suggest the primary role of the intestinal mucosa inflammation in the pathogenesis of neonatal feeding intolerance under conditions of hypoxia in perinatal pathology. It is accompanied by decreased enzymatic activity, weakened local immunity, and increased intestinal mucosa permeability.